Clinical genomics in inflammatory bowel disease - Uhlig, H; Muise, A (Elsevier, 2017)
Genomic technologies inform the complex genetic basis of polygenic inflammatory bowel disease (IBD) as well as Mendelian disease-associated IBD. Aiming to diagnose patients that present with extreme phenotypes due to monogenic forms of IBD, genomics has progressed from 'orphan disease' research towards an integrated standard of clinical care. Advances in diagnostic clinical genomics are increasingly complemented by pathway-specific therapies that aim to correct the consequences of genetic defects. This highlights the exceptional potential for personalized precision medicine. IBD is nevertheless a challenging example for genomic medicine because the overall fraction of patients with Mendelian defects is low, the number of potential candidate genes is high, and interventional evidence is still emerging. We discuss requirements and prospects of explanatory and predictive clinical genomics in IBD.